FLOW RATE MEASUREMENT WITH PROPER INSTRUMENT FOR CANALS IN BANGKOK - Klanpoch, Somsak; Somboon, Vichai; Sricoth, Theeta (Vajira Medical Journal : Journal of Urban Medicine, 2019)
Objective : To find the proper instrument for measuring the flow rate of canals in Bangkok and also to define the flow efficiency by maximum flow rate estimation in two major canals in Bangkok namely Klong Lat Prao and Klong Tawewattana. Methods : Three kinds of flow rate measurement instruments used were ADCP : River Ray, Electromagnetic : AEM1-D, and Magnetic : FP-01 1212 which were borrowed / obtained from different authorities. These instruments were tested in 2 different stations in Klong Prapa. This was to find the most proper instrument to apply for the research. To analyzing flow efficiency in canals was to survey the cross section and the longitudinal section (profiles) and then chosen the flow measurement station. In this research the measurement period tried to cover different flow situations in the 2 canals for each data measurement set. The estimation of flow efficiency was analyzed under 2 methods : the rating curve analysis and the Manning’s Formula. Results : The result identified the ADCP as the most proper instrument because its measurement gave the least different when compared with the existing standard flow instrument belonging to the Metropolitan Water Work Authority which provided easy and quick use for field work. For Klong Tawewattana, quantity and quality of water in canal provided better conditions for the measurement work than in Klong Lat Prao where the researcher could not work as well in a similar situation due do the accumulated sediment at the canal bottom along with floating debis garbage with caused problems to the instrument. Also, several areas of illegal housing obstructed the researcher’s approach to the site. The estimation of flow efficiency in both canals was analyzed under 2 methods : the rating curve analysis and the Manning’s Formula. Both methods provided not much difference in results of maximum flow rate in both canals. Conclusions : The flow rate measurement instruments must be chosen to suit with the type and flow characteristics of water because canals in Bangkok are polluted and so many floating garbages. The flow rate estimation by Manning’s Formula gives the acceptable results compare with results by measurement instruments.